Strategi Regulasi Emosi Cognitive Reappraisal dengan Meaningful Work pada Karyawan - Nabila Fadhia Salama; Diah Sofiah; Hikmah Husniyah Farhanindya (JIWA: Jurnal Psikologi Indonesia, 2026)
Jobs in the public service sector require psychological abilities to interpret work positively amid emotional pressure. This study aims to examine the relationship between cognitive reappraisal emotion regulation strategies and meaningful work among employees of the Surabaya City Transportation Agency. The study uses a correlational quantitative approach involving 123 employees who were assessed using the Work and Meaning Inventory (WAMI) and the Emotion Regulation Questionnaire (ERQ). Data analysis was performed using Spearman's rho correlation. The results showed a significant positive relationship between cognitive reappraisal and meaningful work (r = 0.410; p < 0.01). These findings indicate that the ability to cognitively reappraise work situations plays a role in increasing the meaningfulness of work for employees in the public service sector. Keywords: Meaningful work, emotion regulation, cognitive reappraisal, employee, public service Pekerjaan di sektor pelayanan publik menuntut kemampuan psikologis dalam memaknai pekerjaan secara positif di tengah tekanan emosional. Penelitian ini bertujuan menguji hubungan antara strategi regulasi emosi cognitive reappraisal dan meaningful work pada karyawan Dinas Perhubungan Kota Surabaya. Penelitian menggunakan pendekatan kuantitatif korelasional dengan melibatkan 123 karyawan yang diukur menggunakan Work and Meaning Inventory (WAMI) dan Emotion Regulation Questionnaire (ERQ). Analisis data dilakukan menggunakan korelasi Spearman’s rho. Hasil penelitian menunjukkan adanya hubungan positif yang signifikan antara cognitive reappraisal dan meaningful work (r = 0,410; p < 0,01). Temuan ini menunjukkan bahwa kemampuan menilai ulang situasi kerja secara kognitif berperan dalam meningkatkan kebermaknaan kerja pada karyawan sektor pelayanan publik. Kata kunci: Meaningful work, regulasi emosi, cognitive reappraisal, karyawan, pelayanan publik